Free women of color in Spanish colonial New Orleans 1768-1803 - Wegner, Keia (My University, 2007)
Poster examines..."the economic and social mobility of free women of color in Spanish colonial New Orleans through an analysis of notarial documents, wills, acts, and marriage records. These records showed how free women of color's relationships with white upper class males, affected their children and later generations through patterns of economic and social mobility and wealth."
A poster containing visuals and text describing an undergraduate research project completed at the University of Wisconsin--Whitewater.
Keywords: African American women -- Louisiana -- New Orleans -- History -- 18th century; African American women -- Louisiana -- New Orleans -- History -- 19th century; African American women -- Louisiana -- New Orleans -- Social conditions -- 18th century; African American women -- Louisiana -- New Orleans -- Social conditions -- 19th century; Free African Americans -- Louisiana -- New Orleans -- History -- 18th century; Free African Americans -- Louisiana -- New Orleans -- History -- 19th century; Free African Americans -- Louisiana -- New Orleans -- Social conditions -- 18th century; Free African Americans -- Louisiana -- New Orleans -- Social conditions -- 19th century